Anisotropic and Shape-Selective Nanomaterials Structure-Property Relationships - Hunyadi Murph, Simona E.; Larsen, George K.; Coopersmith, Kaitlin J. (Nanostructure Science and Technology, 2017)
This book reviews recent advances in the synthesis, characterization, and physico-chemical properties of anisotropic nanomaterials. It highlights various emerging applications of nanomaterials, including sensing and imaging, (bio)medical applications, environmental protection, plasmonics, catalysis, and energy. It provides an excellent and comprehensive overview of the effect that morphology and nanometric dimension has on the physico-chemical properties of various materials and how this leads to novel applications.